1997
DOI: 10.1123/jsr.6.1.21
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ankle Strength in Functional Ankle Instability

Abstract: The purpose of this study was to determine if there were any differences in ankle range of motion, strength, or work between persons with normal ankles (Normal,n= 14), those with functional ankle instability (FAI,n= 15), and those with a history of FAI who have been through formal proprioceptive rehabilitation (Rehab,n= 14). A second puipose was to determine normative values for ankle strength and work measurements using the Biodex® isokinetic system. There were no significant differences between groups for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 9 publications
5
44
2
Order By: Relevance
“…6 However, the previous literature related to the presence of peroneal deficits in individuals with functionally unstable ankles is conflicting. 5,8,[13][14][15] Some investigators have identified both concentric 4,13,15 and eccentric 4,15 eversion torque deficits, whereas others have concluded that no eversion deficit exists, regardless of mode or speed of contraction. [7][8][9] Additionally, while the evertor muscles can counter a varus force, 6 proper dynamic stabilization of the ankle can only be achieved through a coordinated effort of all the surrounding muscles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 However, the previous literature related to the presence of peroneal deficits in individuals with functionally unstable ankles is conflicting. 5,8,[13][14][15] Some investigators have identified both concentric 4,13,15 and eccentric 4,15 eversion torque deficits, whereas others have concluded that no eversion deficit exists, regardless of mode or speed of contraction. [7][8][9] Additionally, while the evertor muscles can counter a varus force, 6 proper dynamic stabilization of the ankle can only be achieved through a coordinated effort of all the surrounding muscles.…”
mentioning
confidence: 99%
“…Significant torque deficits have been noted during both concentric 5,11 and eccentric 9,15 muscle contractions, whereas others found no significant invertor deficits. 4,7,10,14,17 Research investigating plantar-flexor and dorsiflexor muscles is very limited. One group 18 studying the plantar flexors reported concentric torque deficits in participants with a history of a lateral ankle sprain; other authors 14 found no significant difference in plantar-flexion or dorsiflexion torque between FAI and control participants.…”
mentioning
confidence: 99%
“…Some studies have identified invertor strength deficits, 107,187,202,218,278 whereas others have not. 156,180 Evertor strength deficits have also been identified in some studies 107,202,242 but not others. 156,180,218,278 Single-Limb Balance…”
Section: Isokinetic Muscle Strength Of Inversion and Eversionmentioning
confidence: 99%
“…156,180 Evertor strength deficits have also been identified in some studies 107,202,242 but not others. 156,180,218,278 Single-Limb Balance…”
Section: Isokinetic Muscle Strength Of Inversion and Eversionmentioning
confidence: 99%
“…[15] McKnight and Armstrong [16] and Baumhauer et al [17] found no significant invertor deficits. Termansen et al [18] studying the plantar-flexors reported concentric torque deficits in participants with a history of a lateral ankle sprain.…”
Section: Introductionmentioning
confidence: 99%